Parametric modeling of blockwall assemblies for automated generation of shopdrawings and detailed estimates using BIM - Zaki, Tarek (AUC Knowledge Fountain, 2016)
The current practice of the produced shopdrawings for masonry walls lack the amount of details needed to ease out the construction process. The typical shopdrawing process is done by extracting layouts and section views from the tender BIM model and add the assembly details (such as vertical rebar, lintel beams, etc.) as 2D geometric shapes on the layouts, which bypasses the features of BIM. Moreover, using the tender BIM model for the procurement and estimation process results in inaccurate estimates, generation of much construction wastes and extra costs borne by the Contractor. Detailed masonry modeling in BIM becomes more challenging when attempting to model the assembly details which is a labor intensive process, time consuming and less rewarding for Contractors; moreover, there is no tool in the market that can automate the generation of masonry assemblies. Thus, this research introduces the development of a wall-assembly model that can automatically generate full virtual constructions of masonry walls in BIM to include all the wall-assembly details. The model could be used for easy extraction of fully detailed shopdrawings, detailed material quantity takeoff for effective procurement plans and for checking modular design issues to minimize wastes in cutting and fitting of the different wall components. The model was designed to include 19 newly developed algorithms that perform query, build and quantity takeoff functions for the different wall components; programmed in a BIM environment using parametric constraint-based modeling technique. The model was validated with a case study project where the as-built shopdrawings, the as-built quantities and the drafting time of the shopdrawings were compared to the model outputs. The results highlight the model’s robust features in terms of: accurately creating shopdrawings exactly similar to the case study’s as-built drawings, providing materials quantity takeoffs with low variances compared to the case study’s as-built quantities and significant productivity improvements in terms of the time required by engineers to draft the shopdrawings and doing quantity estimates. Thus, using this model, a Contractor could significantly improve his productivity, effectively plan for material procurement and generate potential savings in his overhead costs.